Early escitalopram administration as a preemptive treatment strategy against spasticity after contusive spinal cord injury in rats - Youngjae Ryu (Nature Portfolio, 2021)
Abstract In the majority of spinal cord injury (SCI) patients, spasticity develops in the subacute phase and chronically persists with muscle hypertonia. Among various pathological conditions underlying spasticity, upregulated expression of 5-HT receptors (5-HTR) on the spinal motor neurons due to 5-HT denervation is considered one of crucial factors for hyperexcitability of the spinal circuit. As a 5-HT signal modulator, selective serotonin re-uptake inhibitors (SSRIs) are ordinarily prescribed for diseases associated with 5-HT in the CNS, and are known for their ability to increase 5-HT levels as well as to desensitize 5-HTR. Here, we hypothesized that early SSRI administration as a preemptive treatment strategy would effectively prevent the onset of spasticity. We used a rat model of contusive SCI and administered escitalopram during the first 4 weeks after injury, which is the period required for spasticity development in rodent models. We performed a swimming test to quantify spastic behaviors and conducted the Hoffman reflex test as well as histological analyses for 5-HT2AR and KCC2 expressions. Four weeks of escitalopram administration suppressed spastic behaviors during the swimming test and reduced the population of spasticity-strong rats. Moreover, the treatment resulted in decreased immunoreactivity of 5-HT2AR in the spinal motor neurons. Result of the H-reflex test and membrane expression of KCC2 were not significantly altered. In summary, early escitalopram administration could prevent the onset of spastic behaviors via regulation of 5-HT system after SCI, but could not modulate exaggerated spinal reflex. Our results suggest a novel application of SSRIs for preventative treatment of spasticity.